1997
DOI: 10.1016/s0092-8674(00)80505-x
|View full text |Cite
|
Sign up to set email alerts
|

Miranda Is Required for the Asymmetric Localization of Prospero during Mitosis in Drosophila

Abstract: Asymmetric division of Drosophila neuroblasts, sensory organ precursor cells, and cells in the procephalic neurogenic region involves the segregation of Numb and Prospero proteins into one of the two daughter cells. We have isolated a novel gene, miranda, based on the ability of its gene product to interact with the Prospero asymmetric localization domain. miranda expression coincides spatially and temporally with asymmetric cell divisions and asymmetric localization of Prospero. Miranda protein is localized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
224
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(228 citation statements)
references
References 40 publications
4
224
0
Order By: Relevance
“…Studies primarily in the embryonic ventral cord have revealed the mechanism of NB asymmetric divisions, which appears to be conserved between embryonic and larval NBs (for reviews, see Jan and Jan 2001;Betschinger and Knoblich 2004;Wodarz 2005;Yu et al 2006). The asymmetric division of NBs involves the asymmetric localization and segregation of cell fate determinants Numb, Prospero (Pros), Brat, and their adaptor proteins Partner of Numb (Pon) and Miranda (Mira) into the basal GMC (Rhyu et al 1994;Knoblich et al 1995;IkeshimaKataoka et al 1997;Shen et al 1997;Lu et al 1998). During NB asymmetric divisions, the mitotic spindle is oriented along an axis perpendicular to the epithelial layer and an asymmetric spindle is generated to give rise to two unequal-sized daughter cells with distinct cell fates.…”
mentioning
confidence: 99%
“…Studies primarily in the embryonic ventral cord have revealed the mechanism of NB asymmetric divisions, which appears to be conserved between embryonic and larval NBs (for reviews, see Jan and Jan 2001;Betschinger and Knoblich 2004;Wodarz 2005;Yu et al 2006). The asymmetric division of NBs involves the asymmetric localization and segregation of cell fate determinants Numb, Prospero (Pros), Brat, and their adaptor proteins Partner of Numb (Pon) and Miranda (Mira) into the basal GMC (Rhyu et al 1994;Knoblich et al 1995;IkeshimaKataoka et al 1997;Shen et al 1997;Lu et al 1998). During NB asymmetric divisions, the mitotic spindle is oriented along an axis perpendicular to the epithelial layer and an asymmetric spindle is generated to give rise to two unequal-sized daughter cells with distinct cell fates.…”
mentioning
confidence: 99%
“…the coiled-coil Miranda (Mira) protein, the transcription factor Prospero (Pros), the RNA-binding protein Staufen, and its cargo pros mRNA form one complex (Hirata et al, 1995;Ikeshima-Kataoka et al, 1997;Knoblich et al, 1995;Shen et al, 1997;Spana and Doe, 1995) and Partner of numb (Pon) and Numb form another complex (Lu et al, 1998;Rhyu et al, 1994). Formation of the apical cortical domain is necessary for proper basal targeting; loss of Par3-Par6-aPKC components results in a uniform cortical distribution of Pros and Mira at metaphase (Petronczki and Knoblich, 2001;Schober et al, 1999;Rolls et al, 2003;Wodarz et al, 1999).…”
mentioning
confidence: 99%
“…Pros and Brat are not able to directly associate with the cortex but require the adaptor protein Miranda for this function ( Fig. 3) (Ikeshima-Kataoka et al 1997;Shen et al 1997). Miranda is a coiled-coil protein that interacts with both Pros and Brat.…”
Section: Specifying the Differentiated Fate: The Basal Domainmentioning
confidence: 99%